Military and Veteran Mental Health A Comprehensive Guide (Springer New York, 2018)
This authoritative and comprehensive title is designed to enhance best clinical practices for all healthcare providers who care for military service personnel and veterans. The book is organized into four sections. The first section covers foundational information on the culture and context of health care for members of the US military and veteran population. The second section focuses on systems of care for mental health needs of military and veteran populations. The third section characterizes best practices as well as ethical issues in clinical care for mental health needs of members of the military and veterans. Guidance in relation to a wide range of clinical topics is provided, such as mood disorders, post-traumatic stress disorder, combat and operational stress, military sexual assault, psychosis, and sleep disorders. The last section is intended to assist readers in reinforcing their learning through a set of clinical cases with accompanying questions for deeper consideration. An invaluable resource for all clinicians, allied health personnel, and administrators concerned with the mental health needs of service members and veterans, Military and Veteran Mental Health: A Comprehensive Guide is a gold-standard addition to the literature on military healthcare.